2022
DOI: 10.3390/ijms23158209
|View full text |Cite
|
Sign up to set email alerts
|

Chronic-Antibiotics Induced Gut Microbiota Dysbiosis Rescues Memory Impairment and Reduces β-Amyloid Aggregation in a Preclinical Alzheimer’s Disease Model

Abstract: Alzheimer’s disease (AD) is a multifactorial pathology characterized by β-amyloid (Aβ) deposits, Tau hyperphosphorylation, neuroinflammatory response, and cognitive deficit. Changes in the bacterial gut microbiota (BGM) have been reported as a possible etiological factor of AD. We assessed in offspring (F1) 3xTg, the effect of BGM dysbiosisdysbiosis in mothers (F0) at gestation and F1 from lactation up to the age of 5 months on Aβ and Tau levels in the hippocampus, as well as on spatial memory at the early sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…[47] Some preclinical studies have shown that disturbances in gut flora resulting from chronic anti-infective treatment are associated with reduced dementia symptoms in AD as well as reduced Aβ aggregation. [28] However, this finding is inconsistent with the results of other studies. Two months of continuous antibiotic use in middle-aged women can lead to subsequent cognitive decline.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…[47] Some preclinical studies have shown that disturbances in gut flora resulting from chronic anti-infective treatment are associated with reduced dementia symptoms in AD as well as reduced Aβ aggregation. [28] However, this finding is inconsistent with the results of other studies. Two months of continuous antibiotic use in middle-aged women can lead to subsequent cognitive decline.…”
Section: Discussionmentioning
confidence: 62%
“…[7] Certain antibiotics have been found to inhibit amyloid formation and promote depolymerization of Aβ42 oligomers. [28][29][30] Many prospective studies have been conducted on the effects of different antibiotics (including a combination of several antibiotics) on AD. [31] A study combining doxycycline and rifampicin reported improved cognitive function in patients with mild-to-moderate AD using the standardized Alzheimer's Disease Assessment Scale Cognitive Scale (SADAScog) as the primary outcome.…”
Section: Rationalementioning
confidence: 99%
“…Ingestion of high-fibre foods in both the hunter-gatherer and agricultural phase resulted in presence of abundance of Firmicutes and Bacteroidetes . In the urban set up, a rise in Rikenellaceae was observed which if present in abundance is associated with Lupus and Alzheimer’s disease in mice and colorectal cancer in humans (Wang et al, 2021)(Bello-Medina et al, 2022)(Hoang et al, 2022). An imbalance in these gut microbiota might even show implications Autoimmune Diseases, impaired barrier function and mucosal immune dysregulation (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It must be recognized that a potential microbial etiology for neurodegenerative diseases has been postulated for some time, with the oral and gut microbiota particularly implicated, as reviewed extensively elsewhere [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. This has fostered the possibility of the development of suitable bacteria-targeted therapeutic strategies, some of which show promise in animal models [ 80 , 81 , 84 , 85 , 86 ]. It remains to be clarified if it is a general dysbiosis, specific bacteria and their virulence factors, or both that may be most important in the development of Parkinson’s disease, Alzheimer’s disease and other neuropathologies.…”
Section: The Antimicrobial Properties Of Cannabis and Cannabis-derive...mentioning
confidence: 99%